Pengaruh Self Efficacy, dan Kompleksitas Tugas Terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan - Amrih (JURNAL RISET AKUNTANSI JAMBI, 2023)
This study aims to examine the effect of Self Efficacy and task complexity on the auditor's ability to detect fraud at the BPK RI Representative for South Sulawesi Province. This research was conducted at BPK RI Representative of South Sulawesi Province. This study uses primary data by conducting direct research in the field by giving questionnaires/question sheets to 56 respondents who are BPK auditors. The data analysis method used is Structural Equation Model (SEM) analysis. The results showed that: The Self Efficacy variable has a positive but not significant relationship to the auditor's ability to detect fraud, while task complexity has a positive and significant effect on the auditor's ability to detect fraud.